What do men and women envy each other for? - Kimplova, Tereza; Krakovska, Michaela; Badosek, Radim; Cakirpaloglu, Panajotis (Frontiers in Psychology, 2024)
Introduction This study explores the phenomenon of envy directed towards the opposite sex. Envy is a complex emotion that can manifest in various forms, often reflecting societal and biological influences. Previous research suggests a potential imbalance in the domains where men and women experience envy. Methods The research was conducted in the Czech Republic using a demographically representative sample of 1,769 individuals (867 men and 902 women). Respondents were asked what they envied about the opposite sex, and qualitative analysis was performed on their answers. A total of 32 distinct categories of envy were identified. Results The analysis revealed significant differences between men and women in the nature of their envy. Women expressed envy towards men in domains linked to biological conditions and social advantages, such as salary, prestige, physical strength, and the absence of menstruation, childbirth, and menopause. Men, on the other hand, envied women for their physical attractiveness, ease of seduction, ability to perform traditionally female tasks, and motherhood. Some categories, such as safety and tolerance, were shared by both genders, but the underlying reasons differed. For instance, women envied men for not having to fear being alone, while men envied women for being protected by men. Discussion These findings confirm existing evidence of a gender imbalance in envy. The study also uncovered a novel form of envy, termed “ablative envy”, which refers to the desire for the absence of an unpleasant quality. This suggests that envy between the sexes is deeply rooted in both biological and social factors, offering new insights into gender dynamics.